Characterization of mangifera pajang kort, fruit fibres and polysaccharides and their roles in survival and hypocholestrolemic effects of bifidobacteria - Al-Sheragi Mugahed, Sadeq Hasan (2012)
A dried high fiber product from bambangan (Mangifera pajang Kort.) fruit pulp was prepared and evaluated for proximate composition, functional properties, and soluble and insoluble dietary fiber composition. The glucose dialysis retardation index of M.pajang pulp dietary fiber (60) was approximately double than that of cellulose fiber (31.7). These characteristics indicate that M. pajang pulp is a rich source of dietary fiber (87.6 g/ 100g M. pajang pulp fibres) and has physico-chemical properties which make it suitable as a potential food additive in various food products and/or dietetic, low-calorie high-fiber foods to enhance their nutraceutical properties. Polysaccharides were isolated from the fibres pulp of M. pajang Kort . using hot water. Neutral and acidic polysaccharides were separated with DEAE-Cellulose anion-exchange chromatography. Size exclusion chromatography analysis showed the average molecular weight (MW) of the neutral M. pajang polysaccharides (F1) was (7.1 kDa), and those of three acidic polysaccharides (F2, F3 and F4) were approximately 12.6, 24 and 9.4 KDa,respectively. The monosaccharide compositions of these polysaccharides were determined using high performance liquid chromatography. F1 contained erythrose,rhamnose, arabinose, mannose, fructose and glucose (5, 7, 21, 42, 4 and 21 mg/100mg fraction respectively), F2 consisted of rhamnose, xylose and arabinose (33, 7 and 51 mg/100mg fraction respectively), F3 consisted of fructose (14 mg/100mg fraction) and glucose (72 mg/100mg fraction), and F4 comprised arabinose, mannose, fructose and glucose (32, 36, 2 and 10 mg/100mg fraction respectively). Results derived from Fourier transform infrared spectroscopy and the monosaccharide composition analysis suggested that the fibres pulp of M. pajang fruit consisted of heteropolysaccharide and belongs to –type of the pyran group. Additionally, this crude polysaccharide and its fractions showed strong prebiotic properties. The viability and activity of Bifidobacterium pseudocatenlatum G4 and Bifidobacterium longum BB536 were studied in yoghurt containing 0.75% (w/v) of M. pajang fibres polysaccharide (MPFP). Growth of probiotics, their proteolytic activities, the development of short chain fatty acids, pH and viscosity of yoghurts were determined during storage at 4°C for 28 d. B. longum BB536 and B. pseudocatenulatum G4 showed better growth around 8.3 and 8.5 log CFU/mL respectively, in the presence of prebiotics. The activity of B. longum BB536 and B. pseudocatenulatum G4 significantly improved thereby the production of propionic acid (8.2mg/ mL) and proteolytic activity (0.97) of probiotic organisms significantly increased. The viscosity of probiotic yoghurtssignificantly (p < 0.05) increased (1.78 mPa.s) when MPFP was added. The effect of yoghurt supplemented with B.pseudocatenulatum G4 or B. longum BB536 in the presence of MPFP on plasma lipids, lipid peroxidation and the faecal excretion of bile acids was determined in rats fed on a cholesterol-enriched diet. Results showed a significant (p < 0.05) increased in levels of plasma total cholesterol (TC) in positive control (PC) group (7.01 mmol/L) as compared to the negative control (NC) group (2.4 mmol/L), low-density lipoprotein cholesterol (LDL-C) was 4.56 mmol/L in PC and 0.97 mmol/L in NC also plasma malondialdehyde (MDA) levels were 3.98 nmol/L in PC and 1.72 nmol/L in NC after 8 weeks. Atherosclerotic index, triglyceride (TG), and the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), urea and creatinine significant (p < 0.05) increased in positive control (PC) group as compared to the negative control (NC) group after 4 and 8 weeks. However, the groups fed on a cholesterol-enriched diet supplemented with yoghurt containing B. pseudocatenulatum G4 or B. longum BB536 with or without MPFP and inulin as a prebiotics had significantly lower levels of plasma TC, LDL, very low-density lipoprotein cholesterol (VLDL-C), atherosclerotic index, TG, MDA and the activities of ALT, AST, urea and creatinine than the positive control (PC) group at week 4 and 8 of the treatment. The levels of TC, LDL-C and MDA in group consumed yoghurt containing B. pseudocatenulatum G4 with MPFP were 2.42 mmol/L, 0.84 mmol/L and 1.29 nmol/L respectively. In addition, the faecal excretions of bile acids were markedly promoted in yoghurt containing B. pseudocatenulatum G4 or B. longum BB536 groups with or without MPFP or inulin compared PC and NC groups. The concentration of cholic acid in PC and NC was 28.67 and 28.79 mg/g faeces and significantly (p < 0.05) increased in group consumed B. pseudocatenulatum G4 with MPFP 34.64 mg/g faeces. It is noteworthy from the data that the presence of MPFP and inulin were more effective. The effect of MPFP on the survival activity and hypocholesterolaemic effects of bifidobacteria was consistent with that of inulin (a commercial prebiotic) thus MPFP could be added to fermented dairy instead of inulin.M. pajang polysaccharides significantly stimulated the growth of B. longum BB536 and B. pseudocatenulatum G4; however no effect on the growth of Salmonella choleraesuis JCM 6977 and Escherichia coli ATCC 35922. B. longum BB536 and B.pseudocatenulatum G4 had a positive effect on the lipid profile and bile acids of the rats.